2018
DOI: 10.1007/s10658-018-1539-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification and pathogenicity assessment of Colletotrichum isolates causing bitter rot of apple fruit in Belgium

Abstract: Worldwide Colletotrichum spp. have been identified as a problem in the apple production. This is the first study executed and confirming the presence of Colletotrichum spp. causing the postharvest disease bitter rot on apple fruits in Belgium. The identification, genetic diversity of Colletotrichum isolates (present in Belgian apple orchards) their morphological traits and pathogenicity on two apple cultivars (cvs. Pinova and Nicoter) with a different level of susceptibility were studied. Based on sequence ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…is a widespread fruit disease occurring in most countries where apples are cultivated (Shi et al 1996). C. acutatum species complex (SC) infections on apples in Europe are frequently reported with increasing numbers of recent reports from Belgium, England, Italy, France, Norway and Slovenia (Børve and Stensvand 2015;Grammen et al 2019;Mari et al 2012;Munda 2014;Munir et al 2016;Nodet et al 2016). Studies from Germany and Sweden describe postharvest losses of apple fruits of 10 and 25%, respectively, by C. acutatum SC (Børve and Stensvand 2017;Weber and Palm 2010).…”
Section: Colletotrichum Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…is a widespread fruit disease occurring in most countries where apples are cultivated (Shi et al 1996). C. acutatum species complex (SC) infections on apples in Europe are frequently reported with increasing numbers of recent reports from Belgium, England, Italy, France, Norway and Slovenia (Børve and Stensvand 2015;Grammen et al 2019;Mari et al 2012;Munda 2014;Munir et al 2016;Nodet et al 2016). Studies from Germany and Sweden describe postharvest losses of apple fruits of 10 and 25%, respectively, by C. acutatum SC (Børve and Stensvand 2017;Weber and Palm 2010).…”
Section: Colletotrichum Sppmentioning
confidence: 99%
“…(Blazek et al 2007;Hortova et al 2014;Soto-Alvear et al 2013) and for Colletotrichum spp. (Biggs and Miller 2001;Grammen et al 2019). Unravelling resistance mechanisms in fruits can be very helpful to make progress in breeding programs.…”
Section: Breeding For Resistant Cultivars To Postharvest Diseasesmentioning
confidence: 99%
“…The CBD pathogen was placed along with non-CBD causing isolates into two subspecies within C. kahawae. This taxonomic framework led, in recent years, to the identification of "C. kahawae" (no subspecies given) in other hosts and regions [32][33][34][35], raising concern among plant pathologists dealing with coffee diseases, especially when the spread of C. kahawae out of Africa is so feared [13].…”
Section: Discussionmentioning
confidence: 99%
“…is a widespread fruit disease occurring in most countries where apples are cultivated (Shi et al, 1996). C. acutatum species complex (SC) infections on apples in Europe are frequently reported with increasing numbers of recent reports from Italy, Belgium, Slovenia, England, Norway and France (Børve and Stensvand, 2015;Grammen et al, 2018;Mari et al, 2012;Munir et al, 2016;Nodet et al, 2016). Studies from Germany and Sweden describe postharvest losses of apple fruits of 10 and 25%, respectively, by C. acutatum SC (Børve and Stensvand, 2017;Weber and Palm, 2010).…”
Section: Colletotrichum Sppmentioning
confidence: 99%
“…Fruit cultivars may show a large variation in susceptibility to (latent) postharvest diseases (Tian et al, 2016), as was demonstrated among apple cultivars for Colletotrichum spp. (Biggs and Miller, 2001;Grammen et al, 2018) and bull's eye rot caused by Neofabraea spp. (Blazek et al, 2003;Hortova et al, 2014;.…”
Section: Breeding For Resistant Cultivars To Postharvest Diseasesmentioning
confidence: 99%